MOTIVATIONAL FACTORS RELATED TO THE PERFORMANCE OF NURSES IN THE INPATIENT INSTALLATION AT RUMAH SAKIT TERPADU (RST) DOMPET DHUAFA BOGOR IN 2023 - Alda Cahya Kumala Sari; Fini Fajrini (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Nurse performance is a work behavior carried out by nurses in providing nursing care to patients in which there is an implementation of an action plan so that the patient's needs are met optimally. Based on the results of a previous study at RST Dompet Dhuafa Bogor, 65.2% of nurses experienced poor performance. This study aims to find out "Motivational Factors Related to Nurse Performance in Inpatient Installations at RST Dompet Dhuafa Bogor in 2023". The research was conducted in November 2022 - May 2023 at RST Dompet Dhuafa Bogor. This study uses a cross-sectional study design. The population in this study is all nurses who work at RST Dompet Dhuafa Bogor.  The sample of this study was 86 nurses using total sampling. The data in this study used an instrument in the form of a questionnaire, then analysis was carried out using the Chi Square test with α=0.05. The results of the study showed that there was no relationship between job promotion and nurse performance (p-value 0.226), there was a significant relationship between responsibility and nurse performance (p-value 0.000), and there was no relationship between salary and nurse performance (p-value 0.244). There is a relationship between motivation and nurse performance, namely responsibility. Meanwhile, job promotions and salaries have nothing to do with nurse performance. Hospitals provide job promotions regularly every year, make regulations and policies or programs regarding discipline in services to be more responsible, and provide additional bonuses to nurses.